2021
DOI: 10.1016/j.tranon.2020.100924
|View full text |Cite
|
Sign up to set email alerts
|

A signature of 17 immune-related gene pairs predicts prognosis and immune status in HNSCC patients

Abstract: Highlights We utilized multidimensional bioinformatics methods to validate the robustness of prognostic value for our 17 IRGPs signature and explored the relationship between the IRGPs model and immune status. The low-risk group demonstrated a distinctly favorable prognosis, including OS, DSS, and PFS. Through comparing PD-L1, MSI, and TIDE between high and low risk groups, low-risk group was much more sensitive to immunotherapy. Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Gene pair is an expression of the targeted and reference genes from the one sample. Signatures that resemble gene pairs have been used in prognostic evaluations of various cancers [30] , [31] , [32] , [33] . Moreover, the concordance between the 1p/19 codeletion-associated immune prognostic signature developed in our earlier study [6] and the current gene pairs signature was greatly improved than that of the EORTC and RTOG criteria [5] .…”
Section: Discussionmentioning
confidence: 99%
“…Gene pair is an expression of the targeted and reference genes from the one sample. Signatures that resemble gene pairs have been used in prognostic evaluations of various cancers [30] , [31] , [32] , [33] . Moreover, the concordance between the 1p/19 codeletion-associated immune prognostic signature developed in our earlier study [6] and the current gene pairs signature was greatly improved than that of the EORTC and RTOG criteria [5] .…”
Section: Discussionmentioning
confidence: 99%
“…While the presence of abundant tumor infiltrating lymphocytes is generally associated with improved prognosis ( Figure 3 ), differences have been reported according to anatomic subsite, tumor compartment and depending on the HPV status [ 28 ]. Numerous groups addressed the prognostic value of immune-related gene signatures in primary HNSCC and provided growing evidence for a pivotal correlation between molecular immune subgroups and prognostic risk assessment for HNSCC patients [ 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 ]. Though most studies made use of similar transcriptome and clinical data, in particular from TCGA-HNSC the diversity of clinically-relevant immune-related gene signatures is quite high with only minor or no overlap in selected candidate genes.…”
Section: Immune-related Gene Signaturesmentioning
confidence: 99%
“…However, most patients of LUAD are still not sensitive to immune checkpoint inhibitors ( Wang et al, 2020 ). Recent studies have shown that the remodeling of TME plays an important role in the development of LUAD, weakening the response of LUAD patients to immunotherapy ( Jiang et al, 2021 ). Thus, the identification of essential genes that could affect the TME is urgently needed.…”
Section: Introductionmentioning
confidence: 99%